Arthroscopic trans-osseous rotator cuff repair - Chillemi, Claudio (Muscles Ligaments Tendons J, 2017)
BACKGROUND: Mechanical factors are at the basis of any tendon healing process, being pressure an aspect able to positively influence it. For this reason transosseous rotator cuff repair represents the gold standard procedure for patients affected by a cuff tear, maximizing the tendon footprint contact area and reducing motion at the tendon to bone interface. METHODS: The Authors present an all arthroscopic suture bridge-like transosseous repair with the preparation of a single transosseous tunnel perfor med thanks to a precise dedicated instrument (Compasso®) and one implant (Elite-SPK®) with the use of only 3 suture wires. In addition this technique permits to accurately prepare the bony side of the lesion without any risk or complication, such as anchor pull-out and greater tuberosity bone osteolysis. CONCLUSIONS: However, even if this technique seems less demanding, the arthroscopic transosseous repair is still an advanced procedure, and should be performed only by well prepared arthroscopic shoulder surgeons. LEVEL OF EVIDENCE: V.